Temporal unpredictability of a stimulus sequence and the processing of neutral and emotional stimuli - Koppe, Georgia; Bohus, Martin; Kirsch, Peter (NeuroImage, 2015)
Most experimental settings in cognitive neuroscience present a temporally structured stimulus sequence, i.e., stimuli may occur at either constant and predictable or variable and less predictable inter-stimulus intervals (ISIs). This experimental feature has been shown to affect behavior and activation of various cerebral structures such as the parietal cortex and the amygdala. Studies employing explicit or implicit cues to manipulate predictability of events have shown that unpredictability particularly accentuates the response to events of negative valence. The present study investigates whether the effects of unpredictability are similarly affected by the emotional content of stimuli when unpredictability is induced simply by the temporal structure of a stimulus sequence, i.e., by variable as compared to constant ISIs. In an fMRI study, we applied three choice-reaction-time tasks with stimuli of different social-emotional content. Subjects (N=30) were asked to identify the gender in angry and happy faces, or the shape of geometric figures. Tasks were performed with variable and constant ISIs. During the identification of shapes, variable ISIs increased activation in widespread areas comprising the amygdala and fronto-parietal regions. Conversely, variable ISIs during gender identification resulted in a decrease of activation in a small region near the intraparietal sulcus. Our findings reveal that variability in the temporal stimulus structure of an experimental setting affects cerebral activation depending on task demands. They suggest that the processing of emotional stimuli of different valence is not much affected by the decision of employing a constant or a variable temporal stimulus structure, at least in the context of implicit emotion processing tasks. In contrast, temporal structure diversely affects the processing of neutral non-social compared to emotional stimuli, emphasizing the relevance of considering this experimental feature in studies which aim at differentiating social-emotional from cognitive processing in general, and more particularly, aim at identifying circumscribed alterations of social cognition in mental disorders.
Gesehen am 15.03.2018